Does the gene matter? Genotype‐phenotype and genotype‐outcome associations in congenital melanocytic naevi. (3rd February 2020) - Polubothu, S.; McGuire, N.; Al‐Olabi, L.; Baird, W.; Bulstrode, N.; Chalker, J.; Josifova, D.; Lomas, D.; O'Hara, J.; Ong, J.; Rampling, D.; Stadnik, P.; et al.
Summary: Congenital melanocytic naevi (CMNs, commonly known as "moles") are made up of pigment cells which contain a gene that has undergone an alteration (mutation). We know that different moles have different genetic mutations (or "genotypes"), and also that different moles look and behave differently, that is they have different "phenotypes". Very rarely a CMN can be linked with problems in the brain or can even develop into a malignant tumour (melanoma). These researchers in London reviewed 156 CMNs from 134 children to see whether specific genotypes cause particular phenotypes. These children tended to have a more serious phenotype: 76% had two or more CMNs at birth, most had large CMNs, eight had malignant melanoma and 29% had an abnormality on their brain MRI scan. Regarding genotype, 68% of moles had a mutation in the NRAS gene, 7% in the BRAF gene and 25% in neither. Where two different moles were studied from the same patient, they had the same genotype. The study did not show any relationship between genotype and either malignancy or neurological problems. However, larger moles usually had mutations in NRAS while lumpy moles occurred mostly with BRAF mutations and not with NRAS. Examination of lumpy moles under the microscope showed that the lumps were composed not of CMN cells but of fat and connective tissue with the CMN tissue stretched over the top. The authors conclude that genetic testing of moles is unnecessary although it has proved useful in malignant melanoma where genotype can guide treatment options. This summary relates to the study: Does the gene matter? Genotype‐phenotype and genotype‐outcome associations in congenital melanocytic naevi Abstract : Linked Article:  Polubothu et al. Br J Dermatol 2020; 182 :434–443